Antidepressant and antipsychotic medication errors reported to United States poison control centers. Issue 8 (8th May 2018) - Kamboj, Alisha; Spiller, Henry A.; Casavant, Marcel J.; Chounthirath, Thitphalak; Hodges, Nichole L.; Smith, Gary A.
Abstract: Purpose: To investigate unintentional therapeutic medication errors associated with antidepressant and antipsychotic medications in the United States and expand current knowledge on the types of errors commonly associated with these medications. Methods: A retrospective analysis of non‐health care facility unintentional therapeutic errors associated with antidepressant and antipsychotic medications was conducted using data from the National Poison Data System. Results: From 2000 to 2012, poison control centers received 207 670 calls reporting unintentional therapeutic errors associated with antidepressant or antipsychotic medications that occurred outside of a health care facility, averaging 15 975 errors annually. The rate of antidepressant‐related errors increased by 50.6% from 2000 to 2004, decreased by 6.5% from 2004 to 2006, and then increased 13.0% from 2006 to 2012. The rate of errors related to antipsychotic medications increased by 99.7% from 2000 to 2004 and then increased by 8.8% from 2004 to 2012. Overall, 70.1% of reported errors occurred among adults, and 59.3% were among females. The medications most frequently associated with errors were selective serotonin reuptake inhibitors (30.3%), atypical antipsychotics (24.1%), and other types of antidepressants (21.5%). Most medication errors took place when an individual inadvertently took or was given a medication twice (41.0%), inadvertently took someone else's medication (15.6%), or took the wrong medication (15.6%). Conclusions: This study provides a comprehensive overview of non‐health care facility unintentional therapeutic errors associated with antidepressant and antipsychotic medications. The frequency and rate of these errors increased significantly from 2000 to 2012. Given that use of these medications is increasing in the US, this study provides important information about the epidemiology of the associated medication errors.